2014
DOI: 10.1186/2193-1801-3-483
|View full text |Cite
|
Sign up to set email alerts
|

Medication and falls in elderly outpatients: an epidemiological study from a German Pharmacovigilance Network

Abstract: The aim of this study was to investigate the relationship between fall risk increasing drugs (FRIDS) and the risk of falls in regard to fall-related chronic diseases. In total, 39 primary care physicians in Germany participated in the EvaMed Pharmacovigilance Network. Antihypertensives, non-steroidal anti-inflammatory drugs, hypnotics and sedatives, antidepressants and psycholeptics were labelled as FRIDS. A fall was defined according to a diagnosis in the chapter Injury or poisoning (S00-T14 in International … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Additionally, the guidelines recommend checking for orthostatic hypotension, visual impairment, and cognitive impairment as well as review of psychoactive medications. However, use of the guidelines relies on in-person clinical evaluation and often only takes into account a small portion of the risk factors among medications, 710 diagnoses, 8,11 and social issues. 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the guidelines recommend checking for orthostatic hypotension, visual impairment, and cognitive impairment as well as review of psychoactive medications. However, use of the guidelines relies on in-person clinical evaluation and often only takes into account a small portion of the risk factors among medications, 710 diagnoses, 8,11 and social issues. 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Sample size was calculated according to the best-found evidence at the moment of the study design: a study conducted in a community setting with patients older than 65 years (mean age 73 years) who went to a primary care center due to a fall, and were followed for 2 years. 26 According to this study, the risk of falling was 12.4% and 6.1% for those patients who have been using FRIDS and for those patients who have not been, respectively. Supposing a higher risk of falling for the participants in our study, as they are 80 years old or more and have suffered from a previous hip fracture, we estimate, considering the same proportion of risk as in the aforementioned study, that 40% of patients in treatment with FRIDS and 20% without FRIDS will fall.…”
Section: Methodsmentioning
confidence: 62%
“…Fifteen studies showed no association: QA 6.9 (range 4–10) ( 33 , 37 , 60 , 61 , 67 , 68 , 76 , 81 , 83 , 85 , 88 , 129 , 168 , 171 , 176 ). Eight identified a positive association: QA 6.8 (range 4–8) ( 40 , 47 , 49 , 51 , 59 , 100 , 169 , 177 ) ( Supplementary Table 7 ).…”
Section: Resultsmentioning
confidence: 99%
“…Seventeen studies reported no association: QA 7.2 (range 5–10) ( 35 , 38 , 53 , 54 , 64 , 82 , 86 , 89 , 109 , 112 , 125 , 126 , 156 , 209–212 ). Thirteen reported a positive association: QA 6.9 (range 4–8) ( 47 , 65 , 66 , 69 , 74 , 94 , 102 , 163 , 172 , 177 , 206 , 213 , 214 ) ( Supplementary Table 13 ). The majority of studies reported no association with falls.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation